Liquefied natural gas for civil aviation - Rompokos, Pavlos; Kissoon, Sajal; Roumeliotis, Ioannis; Nalianda, Devaiah; Nikolaidis, Theoklis; Rolt, Andrew Martin (MDPI, 2020)
The growth in air transport and the ambitious targets in emission reductions set by advisory agencies are some of the driving factors behind research towards new fuels for aviation. Liquefied Natural Gas (LNG) could be both environmentally and economically beneficial. However, its implementation in aviation has technical challenges that needs to be quantified. This paper assesses the application of LNG in civil aviation using an integrated simulation and design framework, including Cranfield University’s aircraft performance tool, Orion, and engine performance simulation tool Turbomatch, integrated with an LNG tank sizing module and an aircraft weight estimation module. Changes in tank design, natural gas composition, airframe changes, and propulsion system performance are assessed. The performance benefits are quantified against a Boeing 737–800 aircraft. Overall, LNG conversion leads to a slightly heavier aircraft in terms of the operating weight empty (OWE) and maximum take-off weight (MTOW). The converted aircraft has a slightly reduced range compared to the conventional aircraft when the maximum payload is considered. Compared to a conventional aircraft, the results indicate that although the energy consumption is increased in the case of LNG, the mission fuel mass is decreased and CO2 emissions are reduced by more than 15%. These benefits come with a significant reduction in fuel cost per passenger, highlighting the potential benefits of adopting LNG for aviation
Keywords: CO2 emission reduction; short-range aircraft; mission analysis; engine performance; civil aviation; LNG; liquefied natural gas